2015
DOI: 10.1093/rpd/ncv279
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration of local government and experts responding to increase in environmental radiation level due to the nuclear disaster: focusing on their activities and latest radiological discussion

Abstract: Activities were introduced in Kashiwa city in the Tokyo metropolitan area to correspond to the elevated environmental radiation level after the disaster of the Fukushima Daiichi nuclear power plant. These were based on a strong cooperation between local governments and experts. Ambient dose rate and radioactivity of foodstuff produced inside of the city have been monitored. Representative ambient dose rates around living environments have almost already become their original levels of the pre-accident because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The basic or logistical terms, such as IAEA, radioactive strontium, natural background radiation, and half-life, were familiar to residents of Tokyo. We think this is partially attributable to higher education level among residents of Tokyo and continuing environmental contamination with radioactive substances in the Tokyo metropolitan area [ 5 , 6 ]. In terms of the geographical difference, a previous study showed that students in Miyagi had higher levels of trust in institutions as compared to that among students in Tokyo [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic or logistical terms, such as IAEA, radioactive strontium, natural background radiation, and half-life, were familiar to residents of Tokyo. We think this is partially attributable to higher education level among residents of Tokyo and continuing environmental contamination with radioactive substances in the Tokyo metropolitan area [ 5 , 6 ]. In terms of the geographical difference, a previous study showed that students in Miyagi had higher levels of trust in institutions as compared to that among students in Tokyo [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some parts of the Kanto area continue to show elevated environmental radiation levels, the ambient dose rate and radioactive contamination of foodstuffs produced inside the city have been monitored [ 5 ]. Iimoto et al reported that representative ambient dose rates around residential areas have almost returned to the original pre-accident levels because of the decontamination activities, natural washout, and the low effective half-lives of radioactivity [ 6 ]. In 2003, the Food Safety Basic Law was established in Japan to address food safety issues such as bovine spongiform encephalopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Screening to determine contamination was accomplished primarily with the use of hand-held scanners and whole-body counter technologies. Surveillance of radionuclide contamination in the food supply and the environment was used and continues to be used to model predicted biological exposures in the population ( 112114 ). While there is an increasing body of evidence that the exposure levels received from radionuclide fallout from Fukushima were too low to increase cancer risk, there is significant unresolved psychosocial and mental stress in the population experiencing the event and over 350,000 individuals are currently being monitored for possible effects of low-dose radiation over their lifespans ( 115 ).…”
Section: Fukushima and Beyondmentioning
confidence: 99%
“…The accident at the Fukushima Dai-ichi Nuclear Power Plant (NPP) after the Great East-Japan Earthquake (11 March 2011) elevated the background level of environmental radiation in the Tokyo metropolitan area to some degree. Kashiwa city, located inside the metropolitan area of Tokyo and located ~200 km south of the NPP site, with a population of ~0.4 million, was particularly affected [ 1 6 ]. The ambient dose equivalent rate in the city immediately after the accident was ~0.1–1 μSv/h, and the maximum natural background level was ~0.04 μSv/h at that time.…”
Section: Introductionmentioning
confidence: 99%